Professional Qualifications Recognition of Doctors in the EU: A Perspective of EU Citizens and Third-Country Nationals - Šuta, Živa; Pišek Šuta, Karmen (Medicine, Law & Society, 2023)
This article explores the applicable rules in the context of professional qualifications recognition of doctors in the EU. In the pursuit of this examination, it focuses on two groups of individuals, namely EU citizens and third-country nationals, and differentiates between qualifications obtained in the EU and qualifications obtained outside EU. While EU citizens are generally free to pursue their medical profession in any EU Member State, third-country nationals experience difficulties in the recognition of their professional qualifications as they fall outside the scope of specific rules on professional qualifications recognition and do not enjoy free movement rights. The assessment of the applicable rules is followed by a conclusion that the EU citizens are protected under the EU legal framework for the recognition of professional qualifications, however, the legal framework for the recognition of foreign professional qualifications is still absent and depends largely upon general rules applicable to third-country nationals willing to settle and work in the EU.